Psychological Profile of the Military Student: Turkey's Example. (13th May 2015) - Caya, Sinan
Abstract: In the Armed Forces, privates (plain soldiers), the bulk of the man-power, are the conscripts. The hard core consists of the non-commissioned and commissioned rank holders, the professional cadres. They are trained in military schools. The formation of the cadet profile emerges through formal training and education as well as informal influences deriving from their own interaction among themselves. In addition to such internal shaping forces, external factors defined by the country's socio-cultural and economic situation also come into play.